High Operating Voltage Supercapacitor Using PPy/AC Composite Electrode Based on Simple Dipping Method - Kyoungho Kim (Journal of Chemistry)
As various wearable devices are emerging, self-generated power sources, such as piezoelectric generators, triboelectric generators, and thermoelectric generators, are of interest. To adapt self-generated power sources for application devices, a supercapacitor is necessary because of the short generation times (1–10 ms) and low generated power (1–100 μW) of self-generated power sources. However, to date, supercapacitors are too large to be adapted for wearable devices. There have been many efforts to reduce the size of supercapacitors by using polypyrrole (PPy) for high energy supercapacitor electrodes. However, these supercapacitors have several disadvantages, such as a low operating voltage due to the use of an aqueous electrolyte, and complex manufacturing methods, such as the hydrogel and aerosol methods. In particular, the low operating voltage (~1.0 V) is a significant issue because most electronic components operate above 3.0 V. In this study, we successfully demonstrated the high operating voltage (3.0 V) of a supercapacitor using a PPy/activated carbon (AC) composite electrode based on the chemical polymerization of the PPy by simple dipping. In addition, a twofold enhancement of its energy density was achieved compared with conventional supercapacitors using AC electrodes.